Recent approaches in clinical applications of 3D printing in neonates and pediatrics - V S, Sukanya; Panigrahy, Nalinikanta; Rath, Subha Narayan (European journal of pediatrics, 2021)
Neonates and pediatric populations are vulnerable subjects in terms of health. Proper screening and early optimal treatment would reduce infant and child mortality, improving the quality of life. Researchers and clinicians all over the world are in pursuit of innovations to improve the medical care delivery system. Infant morphometrics changes drastically due to the rapid somatic growth in infancy and childhood, demanding for patient-specific customization of treatment intervention accordingly. 3D printing is a radical technology that allows the generation of physical 3D products from digital images and addresses the patient-specific requirement. The combination of cost-effective and on-demand customization offers a boundless opportunity for the enhancement of neonates and pediatric health. Conclusion: The advanced technology of 3D printing proposes a pioneering breakthrough in bringing physiologically and anatomically appropriate treatment strategies addressing the unmet needs of child health problems. What is Known: • The potential application of 3D printing is observed across a multitude of fields within medicine and surgery. • The unprecedented effect of this technology on pediatric healthcare is still very much a work in progress. What is New: • The recent clinical applications of 3D printing provide better treatment modalities to infants and children. • The review provides an overview of the comparison between conventional treatment methods and 3DP regarding specific applications